A cross-sectional study on upright heart rate and BP changing characteristics: basic data for establishing diagnosis of postural orthostatic tachycardia syndrome and orthostatic hypertension. Issue 6 (1st June 2015) - Zhao, Juan; Han, Zhenhui; Zhang, Xi; Du, Shuxu; Liu, Angie Dong; Holmberg, Lukas; Li, Xueying; Lin, Jing; Xiong, Zhenyu; Gai, Yong; Yang, Jinyan; Liu, Ping; et al.
Abstract : Objective: We aimed to determine upright heart rate and blood pressure (BP) changes to suggest diagnostic criteria for postural orthostatic tachycardia syndrome (POTS) and orthostatic hypertension (OHT) in Chinese children. Methods: In this cross-sectional study, 1449 children and adolescents aged 6–18 years were randomly recruited from two cities in China, Kaifeng in Henan province and Anguo in Hebei province. They were divided into two groups: 844 children aged 6–12 years (group I) and 605 adolescents aged 13–18 years (group II). Heart rate and BP were recorded during an active standing test. Results: 95th percentile (P95 ) of δ heart rate from supine to upright was 38 bpm, with a maximum upright heart rate of 130 and 124 bpm in group I and group II, respectively. P95 of δ systolic blood pressure (SBP) increase was 18 mm Hg and P95 of upright SBP was 132 mm Hg in group I and 138 mm Hg in group II. P95 of δ diastolic blood pressure (DBP) increase was 24 mm Hg in group I and 21 mm Hg in group II, and P95 of upright DBP was 89 mm Hg in group I and 91 mm Hg in group II. Conclusions: POTS is suggested when δ heart rate is ≥38 bpm (for easy memory, ≥40 bpm) from supine to upright, or maximum heart rate ≥130 bpm (children aged 6–12 years) and ≥125 bpm (adolescents aged 13–18 years), associated with orthostatic symptoms. OHT is suggested when δ SBP (increase) is ≥20 mm Hg, and/or δ DBP (increase) ≥25 mm Hg (in children aged 6–12 years) or ≥20 mm Hg (in adolescents aged 13–18 years) from supine to upright; or upright BP≥130/90 mm Hg (in children aged 6–12 years) or ≥140/90 mm Hg (in adolescents aged 13–18 years).